Theorizing Internet, Religion and Post Truth: an Article Review - Alimi, Moh Yasir (Universitas Negeri Semarang, 2019)
Landscape of Indonesian politics is overshadowed by wide and massive distribution of hoaxes and bullshits. This article reviews 70 latest articles to answer the following questions: what is underlying behind massive distribution of hoaxes? Why do many Indonesian educated publics believe and share hoaxes?Ã‚Â Why are there more religion-based hoaxes than science or economy sciences based hoaxes in Indonesia? The author finds that the massive distribution of hoaxes and their easy acceptance by Indonesian publics reveals the emergence of post truth, a mind set where emotion is regarded to be more important than fact, evidence, or truth. In religius context, post truth illustrates the distribution of banal religion, un-verified forms religious interpretation, in internet and social media. Political competition during the presidential election accelerates the distribution of religion-based hoaxes.